Interrupção da gravidez por opção da mulher até às 10 semanas: um estudo demográfico - Gomes,Inês (2017)
Overview and Aims: In Portugal, induced abortion for non-medical reasons by woman's choice until 10 weeks of gestation is permitted since 2007, when conducted in official recognized establishments. The main goal was to compare the demography of women admitted for abortion by request, following depenalization and the beginning of the world financial crisis, with the period post-troika, represented by the years 2008 and 2015, respectively. Study design and Population: Retrospective, observational and comparative study of women's clinical files that attended at our service for abortion in 2008 and 2015. Methods: We compared the referral source, women's age, number of previous induced abortions, nationality, place of residence, marital status, progeny, couple cohabitation, literacy, women and partner labor, contraception use and gestational age. Results: Were included 1212 women (2008: 665 and 2015: 547). The mean age was 28,1 vs 27,99 (2008 vs 2015). The results were higher at 2008 than 2015 in couple cohabitation: 52% vs 42% (p=0.001) and contraception use: 74% vs 65% (p=0,002). The results were lower at 2008 than 2015 in number of previous induced abortions: 19% vs 29% (p<0,001), in women inhabiting in the same area of our institution: 87% vs 94% (p <0.001), in unmarried women: 63% vs 77% (p< 0,001), in women with more than third grade of primary school: 76% vs 89% (p <0.001), on unemployment in woman: 17% vs 28% (p=0.002) and partner: 8% vs 19% (p <0.001) and in abortions at 10 weeks: 2% vs 14% (p<0.001). We haven't observed statistically significant alterations on the other cases. Conclusions: Between 2008 and 2015 there was an increase in previous induced abortions, women inhabiting in the same area of our institution, unmarried women, literacy, unemployed woman and partner and gestational age attended for abortion. There was a decrease in couple cohabitation and in contraception use choice until 10 weeks of gestation is permitted since 2007, when conducted in official recognized establishments. The main goal was to compare the demography of women admitted for abortion by request, following depenalization and the beginning of the world financial crisis, with the period post-troika, represented by the years 2008 and 2015, respectively